Ziziphus spina-christi alleviates paracetamol-induced hepatorenal toxicity in rats through in vivo and computational approaches - Ehsan Kh. M. Khedre; Amany M. M. Hegab; Amira A. El-Mahis; Amina A. S. Abdel Rahman; Sherien H. B. Elwakeel; Ali S. Abdelhameed; Vittorio Calabrese; Ursula M. Jacob; Eman S. G. Hassan (Scientific Reports)
Abstract Paracetamol (PCM) overdose is a leading cause of drug-induced liver and kidney injury, necessitating effective therapeutic strategies. This study aimed to evaluate the protective effects of Ziziphus spina-christi (ZSC), a traditional medicinal plant with documented antioxidant and protective properties against PCM-induced hepatorenal toxicity in rats, integrating both in vivo and computational approaches. Male rats were divided into four groups: control (vehicle), PCM (300 mg/kg), ZSC (400 mg/kg), and PCM + ZSC (combined treatment). Treatments were administered daily for 14 days. The study included biochemical analysis of liver and kidney function markers, oxidative stress indicators, histological and immunohistochemical examinations, and molecular docking studies. Statistical significance was determined using one-way ANOVA followed by post hoc tests. PCM administration caused significant increases in liver enzymes, lipid profile, renal markers, and hepatic oxidative stress. It also upregulated the expression of apoptotic proteins (Bax, caspase-3, ERK, JNK, and p38 MAPK) and inflammatory mediators (TNF-α, NF-κB), while downregulating the anti-apoptotic protein Bcl-2. Co-treatment with ZSC significantly reversed these alterations, improving biochemical, histological, and molecular parameters. Molecular docking showed that rosmarinic acid, a major phenolic acid in ZSC, had strong binding affinities with the studied apoptotic and inflammatory targets through various hydrophilic and hydrophobic interactions. ZSC demonstrates significant protective effects against PCM-induced liver and kidney damage, likely through modulation of apoptotic and inflammatory signaling pathways including NF-κB/TNF-α, Bcl-2/Bax/caspase-3, and ERK/JNK/p38 MAPK. These findings support the potential of ZSC as a therapeutic candidate for managing drug-induced hepatorenal toxicity and provides the foundation for clinical testing.